(untitled) (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
The "Popcorn Brain" phenomenon in early childhood is an issue requiring attention amidst rising screen time exposure and digital technology usage. This study aims to analyze the behavioral characteristics associated with Popcorn Brain, pedagogical strategies applicable by early childhood educators, and the challenges and supporting factors regarding their implementation. A literature review method was employed, analyzing 15 scholarly articles selected based on their relevance to screen time, early childhood behavior and cognitive function, instructional strategies, and technology usage guidance. Articles were selected based on topic alignment, publication year, and the availability of information supporting the study’s objectives. The synthesis indicates that excessive screen time exposure is linked to difficulties in sustaining attention, reduced engagement in non-digital activities, and challenges in developing self-control. Applicable strategies include interactive learning, limiting technology use, physical activities, self-control exercises, and face-to-face social interaction. Implementation challenges include varying media usage patterns at home and limited supervision. Parental mediation and consistent rules regarding technology use can help mitigate the potential negative impacts of technology